2017
DOI: 10.1038/aps.2016.120
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of the glucose-lowering effects of berberrubine-9-O-β-D-glucuronide, an active metabolite of berberrubine

Abstract: Berberrubine (BRB) is the primary metabolite of berberine (BBR) that has shown a stronger glucose-lowering effect than BBR in vivo. On the other hand, BRB is quickly and extensively metabolized into berberrubine-9-O-β-D-glucuronide (BRBG) in rats after oral administration. In this study we compared the pharmacokinetic properties of BRB and BRBG in rats, and explored the mechanisms underlying their glucose-lowering activities. C57BL/6 mice with HFD-induced hyperglycemia were administered BRB (50 mg· kg -1 ·d -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…Berberrubine (BRB), an active lipid-lowing metabolite of berberine (Li et al, 2010;Zhou et al, 2014), showed a high proportion of glucuronidation metabolism in vivo in our previous study (Yang et al, 2017a). In our present study, for the first time, based on the specific metabolic pattern of BRB, our data suggested that some important endogenous molecules are potentially effective endogenous inhibitors on mouse renal glucuronidation via the employment of an integrated strategy of metabolomics and pharmacokinetics.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…Berberrubine (BRB), an active lipid-lowing metabolite of berberine (Li et al, 2010;Zhou et al, 2014), showed a high proportion of glucuronidation metabolism in vivo in our previous study (Yang et al, 2017a). In our present study, for the first time, based on the specific metabolic pattern of BRB, our data suggested that some important endogenous molecules are potentially effective endogenous inhibitors on mouse renal glucuronidation via the employment of an integrated strategy of metabolomics and pharmacokinetics.…”
Section: Introductionsupporting
confidence: 54%
“…HFD Decreased the Ratio of BRBG to BRB in Urinary Excretion. A simultaneous assay of BRB and BRBG was developed using an LC-MS/MS analytical approach based on our previous studies (Yang et al, 2017a). The plasma concentration-time curves and urinary excretion of both BRB and BRBG in the three groups (CSB, CMB, and HMB) were investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the major drawback of BBR is the low bioavailability (usually <1% in various species) (Liu et al, 2016), especially considering that high oral doses of BBR (>900 mg/day) carry a risk of clinical gastrointestinal side effects (Yin et al, 2008). Moreover, the major BBR metabolites, M1–M5 (Figure 1A), were also verified to have hypoglycemic activity in cells or animals (Li et al, 2011; Wang K. et al, 2017; Yang et al, 2017). M1 even showed more hypoglycemic capacity than BBR in diabetic animals (Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 88%
“…High‐fat‐diet mice were developed using HFD feeding according to a method described previously with some modifications . Briefly, the mice were allowed for 3‐day acclimation before the initiation of the study and were randomly divided into normal control (CON) group and HFD groups.…”
Section: Methodsmentioning
confidence: 99%